Petrography of the Neogene Siwalik Group sandstones, Khutia Khola section, Nepal Himalaya: implications for provenance, paleoclimate and tectonic setting (Journal of Nepal Geological Society, 2017)
The Neogene fluvial sediment (Siwalik Group) forming the southernmost foothill in the Himalaya is one of the best archives of climate history and uplift of the Himalaya. The petrographic composition of these fluvial sandstones provides information on source rocks, depositional climate of the Siwalik sediments and tectonic setting of the Himalaya. This study presents the petrographical results of the Siwalik sandstones from the Khutia Khola section, Nepal Himalaya. Petrographically, these sandstones are lithic arenites (30%) to sub-litharenites (70%). Provenance analyses show that sediments were mainly derived from recycled orogenic and transitional recycled areas in the recycled orogen block provenances. The climatic indexes suggest the semi-humid to humid climate during sedimentation of the Khutia Khola sandstones. The stratigraphic trend of the lithic components show that metamorphic lithic grains are increasing and sedimentary lithic grains are decreasing in up section, and the Lesser and Higher Himalayas are the mixed source of these Siwalik sandstones.